(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study of hydrological basins is crucial for identifying and estimating surface runoff and associated risks. Various software tools, including Arc GIS, WMS V11.0, and ENVI, were employed to analyze data specific to the Rukram Valley basin and determine its hydrological characteristics. This basin covers an area of 298.7 km², located in the northwest of Dohuk District and west of Dohuk Governorate. The natural data of the basin's soil were analyzed based on laboratory tests. Land use and land cover were classified using satellite imagery through supervised classification. The Soil Conservation Service Curve Number (SCS-CN) method was utilized to estimate the volume of surface runoff using WMS V11.0. The region exhibits four types of hydrological soils (A, B, C, D), and land cover was classified into four categories using data from the American Landsat satellite to derive Curve Number (CN) values, which ranged from 36 to 100, with a weighted average of 61.9. In this study, the SCS-CN model was applied five times using rainfall events ranging from 20 to 100 mm, with increments of 20 mm. Additionally, an actual rainfall event of 86.3 mm on March 17, 2024, was used. The results indicated that a significant portion of the rainfall runs off the surface when rainfall exceeds 60 mm, with the surface runoff depth reaching 21.12 mm for 100 mm of rainfall. The maximum discharge was 400.32 m³/s over 1710 minutes during a 100 mm rainfall event. Surface runoff volumes ranged from 313,215.0 m³ for 20 mm of rainfall to 2,135,283.5 m³ for 100 mm of rainfall.